2019
DOI: 10.1108/lhs-11-2017-0067
|View full text |Cite
|
Sign up to set email alerts
|

Alternative careers at the first level of management

Abstract: Purpose First-line nurse managers are frequently torn between conflicting demands from management and employees, and previous research suggests that nurse managers use a variety of responses to cope with these demands. The purpose of this paper is to explore the influence of social support on nurse managers’ responses to role-conflict. Design/methodology/approach Two focused ethnographic studies involving participant observation and interviews with seven first-line nurse managers were completed. One study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The subarea of Communication includes preparing for and participating in meetings, managing unit meetings, and conversations with personnel. These findings were similar to the results reported by Kirchhoff & Karlsson (2019), more specifically, nurse managers who frequently engage in meetings with management, such as networking with other managers and involvement in managementlevel projects, were less visible in the organizational unit [31]. Several studies have reported that nurse managers need to be visible, accessible, and provide regular feedback to their staff [26,34,35].…”
Section: Job Satisfactionsupporting
confidence: 84%
See 1 more Smart Citation
“…The subarea of Communication includes preparing for and participating in meetings, managing unit meetings, and conversations with personnel. These findings were similar to the results reported by Kirchhoff & Karlsson (2019), more specifically, nurse managers who frequently engage in meetings with management, such as networking with other managers and involvement in managementlevel projects, were less visible in the organizational unit [31]. Several studies have reported that nurse managers need to be visible, accessible, and provide regular feedback to their staff [26,34,35].…”
Section: Job Satisfactionsupporting
confidence: 84%
“…Furthermore, Chen et al (2020) found that nurse managers frequently participate in information management on a daily basis. However, increased workloads among nurse managers have reduced the time they can share with nurses [23,[31][32][33]. This presents a challenge, as nurse managers need to be visible and approachable, as well as give regular feedback to their staff [26,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…They are also required to adhere to the simultaneous realization of multiple roles in managerial tasks entrusted to them. 28,29 This condition makes them to give more weight to one of the roles. Hence the situation leads to role conflict.…”
Section: Role-related Stressorsmentioning
confidence: 99%
“…Burnout has been associated with situational stressors, workload, role stress, role conflict, and ambiguity (Miller et al, 1989;Noh, 2017). Role conflict is defined as two or more conflicting obligations (Kirchhoff & Karlsson, 2019;Miller et al, 1989). Role conflict can be considered a type of SD-nexus, conceptually making burnout an outcome of SD.…”
Section: Sd In Nursingmentioning
confidence: 99%